Presence of Microplastics in Workers of Apis mellifera (Linnaeus, 1758) in Different Landscapes in Brazil - Rodrigues, Karla Fernanda Sanches; Rani-Borges, Bárbara; Ando, Rômulo Augusto; Suffredini, Ivana Barbosa; Smith, Welber Senteio (Water, air, and soil pollution, 2024)
Microplastics (MPs) are pervasive contaminants across all environmental compartments, with the atmosphere garnering significant attention in recent years due to its role as a crucial receptor and transporter of numerous pollutants. Deposition of these particles can occur via dry or humid processes, and their presence has been documented in areas far removed from urban and industrial centers, suggesting long-distance transport of MPs. Much of this transport is facilitated by air masses, which move in tandem with prevailing winds; however, pollinating insects, notably bees, also contribute to this dissemination as they encounter these particles during flight and foraging activities. Thus, the present study aimed to implement an established protocol for MP analysis in bees of the species Apis mellifera , given the limited research in this area within Brazil, and to ascertain whether a contamination gradient exists across three sampling sites (urban, periurban, and rural areas). A total of 505 particles were discovered across the three areas, comprising 307 fibers, 137 fragments, and sixty-one filaments. The PCA analysis indicated that the bees of the four hives located in the urban area and the bees of the two hives located in the peri-urban area had a higher amount of internal microplastic particles. Through the chemical analysis of the particles, 30 spectra were obtained, 13 polyethylene terephthalate (PET), 11 polyamide (PA), 4 polyethylene (PE), 1 polyester (PL) and 1 polyvinyl chloride (PVC) were identified. Graphical Abstract